Tindak Insult pada Kasus Bullying Verbal di Media Sosial Online (Kajian Linguistik Forensik) - Sawidiah, Sawidiah; Ulfa, Mariam (Universitas Muhammadiyah Surabaya, 2025)
This research discusses verbal bulliying in the form of insults, which occurs in online social media. Forensic linguistics as a basis in analyzing insults in an act of bulliying in online social media. This research aims to analyze and as an access used in forensic science through a linguistic point of view in revealing a case of verbal bulliying crimes that are rampant in social media. By using descriptive research, data is collected through documentation in the form of screenshots of posts, comments, or videos, then analyzed to find data that can be used as evidence of verbal bulliying. The results showed that insults as a form of language crime, through words and speech which are then disseminated on various online social media platforms, such as; Instragram, Facebook, Tiktok, and X (Twitter). The findings are expected to make a contribution to the science of language, especially forensic linguistics and a deeper understanding of verbal bulliying in the form of insults on online social media.